Reducing the cleaning time of PM2.5 pollution to WHO-recommended air quality levels with a recirculation filter unit - Oleksandr Pryimak; Liubov Makarenko (Budownictwo o Zoptymalizowanym Potencjale Energetycznym)
The article exams the possibility of reducing the air purification time from finely dispersed PM2.5 particles to meet with WHO recommendations in an office space at a standard temperature and humidity. A recirculation unit equipped with a HEPA11 filter was chosen. The time taken by the recirculation unit to clean the air in the office was measured at two dif-ferent airflow rates. For both airflow rates, two concentrations of PM2.5 pollution needed to be purified: low and dangerous. It was possible to achieve a level of reduction in PM2.5 for the given volume of the room by 97 % from the initial level of pollution. Increasing the frequency of air changes from two to almost six times made it possible to speed up the cleaning process. This reduced the time a person needed to spend in the hazardous environment without requiring significant energy costs.